The Effect Of Debt Covenant, Tunneling Incentive, Bonus Mechanism And Firm Size On Transfer Pricing - Nur Amanah Yulianti; Kimsen Kimsen (UNIVED Press, 2025)
The purpose of this study was to determine the effect of Debt Covenant, Tunneling Incentive, Bonus Mechanism and Firm Size on Transfer Pricing in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2019-2023 period. The population of this study includes all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 28 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. This research uses Eviews 12.0. The result shows that: (1) Debt Covenant affects transfer pricing, (2) Tunneling Incentive affects transfer pricing, (3) Bonus Mechanism has no effect on transfer pricing, (4) Firm Size has no effect on transfer pricing.